2016
DOI: 10.1111/ced.12797
|View full text |Cite
|
Sign up to set email alerts
|

PCR-reverse blot hybridization assay for fast and accurate identification of causative species in superficial fungal infections

Abstract: Compared with KOH preparation or fungal culture, PCR-REBA has higher sensitivity and specificity. Therefore, PCR-REBA could be a useful method in clinical settings because it can identify species quickly and accurately, and can also determine the existence of pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…This study is also significant in that we simultaneously assessed a total of 35 gene variants using REBA with only a small amount of tissue sample. REBA, along with DNA chip assays, has been used not only to identify genotypes of human papilloma virus, mycobacteria and dermatophytes, but also to identify mutations within specific genes . This trial is significant because it is the first application of REBA to identify human disease‐related gene variations, especially in patients with AD with complex gene variations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is also significant in that we simultaneously assessed a total of 35 gene variants using REBA with only a small amount of tissue sample. REBA, along with DNA chip assays, has been used not only to identify genotypes of human papilloma virus, mycobacteria and dermatophytes, but also to identify mutations within specific genes . This trial is significant because it is the first application of REBA to identify human disease‐related gene variations, especially in patients with AD with complex gene variations.…”
Section: Discussionmentioning
confidence: 99%
“…The REBA membrane was designed to contain a total of 70 probes [35 wild‐type (WT) and 35 mutant‐type (MT) probes] to detect these genes, and one control probe for colorimetric signal detection (Table ). REBA was performed in accordance with our previous reports (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR-based REBA is a molecular biologic method that can be used for diagnosing bacterial or fungal species ( 37 40 ). Studies showed that REBA yields fast and reliable results with higher specificity and sensitivity compared with fungal culture or KOH test ( 38 , 40 ). The sensitivity and NPV of the KOH test relative to REBA were only moderate, at 66.2% and 65.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%